Strengthening the Sustainable Creative Economy through Downstreaming and Diversification of Dayak Onion Processed Products and Digital Marketing Strategies - Hety Devita; Siti Rahmayuni; Anwar Arifin Pinem; Melissa Indah Azhari; Azmil Abdillah (Journal of Innovative and Creativity, 2025)
The study purpose was community service activity is to strengthen the creative economy sector based on local potential through the downstream development and diversification of processed bawang dayak (Eleutherine palmifolia) products combined with digital marketing strategies. Bawang dayak is a native plant of Kalimantan that possesses high economic and medicinal value; however, its utilization has been limited to raw materials due to the low technological capacity, limited product innovation, and weak digital marketing skills among local micro, small, and medium enterprises (MSMEs). This program aims to empower partner communities to transform from raw material producers into independent and innovative creative entrepreneurs through a participatory–applicative approach. Materials and methods. The program was implemented with the involvement of 25 participants from the Silaturahmi Herbal Community in Balikpapan, East Kalimantan. The activities consisted of five stages: needs analysis, planning, technical training in product processing and diversification, packaging and branding development, digital marketing training, and evaluation. The methods used included workshops, mentoring, and hands-on practice with continuous monitoring to ensure skill transfer Results. The program resulted in significant improvements in both technical (hard skills) and managerial (soft skills) aspects. Participants successfully developed derivative products such as herbal tea, syrup, capsules, and natural soap with modern packaging and brand identity. Digital marketing training enhanced participants’ ability to manage social media and e-commerce platforms, leading to an average sales increase of 25–30%. The application of technology-based innovation and branding strategies also improved product quality and consumer trust.. Conclusions. he community service program effectively enhanced local MSME capacity in production, innovation, and digital marketing, achieving an 80–90% improvement in skills. It contributed to strengthening the competitiveness of local herbal products and creating a sustainable creative economy ecosystem in East Kalimantan..